Implementation and evaluation of a curriculum on the assessment and treatment of disruptive behaviour disorders. Issue 8 (3rd April 2021) - Doja, Asif; Pringsheim, Tamara; Andrade, Brendan F; Cowley, Lindsay; Healy, Sarah A; Baron, Tara; Chan, Melissa; DiBartolo, Marielena; Gripp, Karen; Manos, Sarah; Silverman, Jason A; Writer, Hilary; et al.
Abstract: Disruptive behaviour disorders (DBDs)—which can include or be comorbid with disorders such as attention-deficit hyperactivity disorder, oppositional defiant disorder, conduct disorder and disruptive mood dysregulation disorder—are commonly seen in paediatric practice. Given increases in the prescribing of atypical antipsychotics for children and youth, it is imperative that paediatric trainees in Canada receive adequate education on the optimal treatment of DBDs. We describe the development, dissemination, and evaluation of a novel paediatric resident curriculum for the assessment and treatment of DBDs in children and adolescents. Pre–post-evaluation of the curriculum showed improved knowledge in participants.